French Role in Conflict Resolution Efforts in Mali - Citra N. Fariaty (Kirana Publisher (KNPub), 2022)
French involvement and efforts to resolve the conflict in Mali is based on French national interest in Mali. French national interest in Mali is to secure the economic interest of natural resources, political interest is to restore France influence on countres in Africa, and security interest is to prevent the Mali transform into a den of terrorist. France has run two strategis to help resolve conflict in Mali, which is through hard power with military intervention and soft power by passing to withdraw aid from other countrues and international organizations.